ANALISIS PERMUKIMAN TRANSMIGRAN DI KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - elva riani riani; ahyuni .; febriandi . (JURUSAN GEOGRAFI FIS UNP, 2018)
Abstract This research type is descriptive with quantitative approach. The population of this research is nagari which become transmigrant settlement Analysis using the nearest neighbor method and buffer analysis with the help of ArcGIS 10.1 software. The results showed that: 1. Transmigrant settlement pattern: a). Nagari Sitiung is random with result of Nearest Neighbor Ratio 1.036077, Nagari Sei Duo is random with result of Nearest Neighbor Ratio 0,901302, Nagari Gunung Medan is random with result of Nearest Neighbor Ratio 1,332495. b). Sitiung Subdistrict is grouped with result of Nearest Neighbor Ratio 0,602739. 2. Reach of services in transmigrant settlements: a). 173 point of settlement Nagari Sitiung, 276 settlement point Nagari Sei Duo, 65 point of settlement Nagari Gunung Medan get education service reach, b). 173 point of settlement Nagari Sitiung, 276 settlement point of Nagari Sei Duo, 24 point of settlement Nagari Gunung Medan get health service reach, while 41 point of settlement Nagari Gunung Medan do not get health service coverage, c). 276 point of settlement Nagari Sei Duo, 168 point of settlement Nagari Sitiung got range of commerce service, while 5 point of settlement Nagari Sitiung, 65 point of settlement Nagari Gunung Medan do not get range of commerce service. Keywords: Analysis, Settlement, Transmigrant